Sensory branding and buying behavior in coffee shops : a study on Generation Y - S Dalle Ave; M Venter; B Mhlophe (The Retail and Marketing Review, 2015)
With the rise of globalisation and the infiltration of global brands into emerging markets, retailers are facing challenges to win market share in this competitive landscape. As a result, retailers are reverting to innovative methods such as experiential marketing to influence consumer buying behaviour. The purpose of this paper is to investigate the effectiveness of using experiential marketing as a way of influencing consumers’ purchase intentions in coffee shops. The influences of scent and sight as predictors of purchase intention among Generation Y consumers is explored. By means of a quantitative study, 256 self-administered questionnaires were distributed amongst Generation Y individuals in Johannesburg. The data analysis was done by means of structural equation modelling (SEM), with the main focus being placed on path modelling for testing the proposed hypotheses. The findings indicate that both scent and sight are predictors of purchase intention. Although several studies have explored this phenomenon in an array of contexts, few studies have investigated Generation Y within a South African context. This paper is of paramount importance to retailers who seek to gain market share in the competitive landscape by implementing innovative ways in a bid to effectively influence consumer buying behaviour.